2006
DOI: 10.1111/j.1365-2699.2005.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of regional species richness: an empirical analysis of the number of hawkmoth species (Lepidoptera: Sphingidae) on the Malesian archipelago

Abstract: Aims  Major patterns and determinants of the species richness of Sphingidae in the Malesian archipelago were investigated, including a distinction of richness patterns between subfamilies and range‐size classes. Location  Southeast Asia, Malesia. Methods  Using a compilation of specimen‐label data bases, geographic information system (GIS)‐supported estimates of distributional ranges for all Sphingidae species of Southeast Asia were used to assess the species richness of islands. Range maps for all species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…Yet, isolation arises as an important factor in shaping island biotas (Heaney et al. , 2005; Beck et al ., 2006a,b), due to two related phenomena acting in opposite directions. More isolated islands will have lower immigration rates and an absence of constant gene flow that might result in a higher frequency of founder effects generating new species on these islands (but see Clegg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, isolation arises as an important factor in shaping island biotas (Heaney et al. , 2005; Beck et al ., 2006a,b), due to two related phenomena acting in opposite directions. More isolated islands will have lower immigration rates and an absence of constant gene flow that might result in a higher frequency of founder effects generating new species on these islands (but see Clegg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biogeographical regions have found increasing use in macroecological investigations of species richness or other macroecological patterns as a way to capture regional idiosyncrasies and historical contingencies above and beyond present‐day environmental correlates (Qian & Ricklefs, 2000; Hawkins et al. , 2003; Beck et al. , 2006a; Buckley & Jetz, 2007; Davies et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies attempting to determine the distribution of individual moth families to changes in vegetation, climate and topography have been conducted in the tropics , Axmacher et al 2004, Beck et al 2006, Hilt and Fiedler 2006, Beck and Chey 2008, but few have examined multi-family diversity and communities. Most of these studies found that both elevation and plant species distributions are important predictors of moth family distributions and diversity patterns.…”
Section: Introductionmentioning
confidence: 99%